Relationship Between Hypertension And Diabetes Mellitus Type 2 With Benign Prostate Hyperplasia In Mgr. Gabriel Manek Hospital Atambua - Wijaya, Adrianus Gupta; Telussa, Arley Sadra (Universitas Nusa Cendana, 2021)
Objectives: To evaluate the relationship between hypertension (HT) and diabetes mellitus type 2 (DM type 2) with benign prostate hyperplasia (BPH).Material & methods:This is a case control study with group A (case) consist of 78 BPH patient and group B (control) consist of 78 non BPH patient. DM and HT status from each group was collected. Correlation between each variables and odds ratio was analyzed.Results: Mean age was 66.09 ± 9.05 and 63.40 ± 9.83 years in group A and group B respectively. There is a statistical significant correlation between HT (0.001) and DM (0.021) with BPH (p<0.05). Patient with hypertension are 7.8 times more likely to suffer from BPH (OR 7.882) and patient with DM are 3 times more likely to suffer from BPH.Conclusion: HT and DM type 2 are significantly related to BPH incidence in Mgr. Gabriel Manek Hospital. Patient with HT and DM type 2 are more likely to suffer from BPH. Prevention and management of HT and DM type 2 may help to reduce the incidence of BPH.